The Cultural Synthesis of Success: An Intrinsic Case Study of a Chinese-Indonesian Entrepreneur and Royal Courtier - Puspitasari, Nungki; Riyono, Bagus (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: In the complex landscape of Indonesian ethnic and economic identity, the convergence of Chinese entrepreneurial spirit and Javanese royal traditions offers a unique lens into the multidimensional nature of success. This study explores the core values of a Chinese-Indonesian entrepreneur who holds the noble title of Kanjeng Mas Tumenggung in the Yogyakarta Palace. Utilizing an intrinsic case study design within a constructivist paradigm, we examine how the subject navigates and synthesizes two distinct cultural orientations. Our findings reveal that success and happiness are driven by a synergy of self-direction, universalism, and benevolence. Critically, the Javanese philosophy of "migunani tumpraping liyan" (being of benefit to others) serves as a catalyst that transforms business ambition into cultural service. This study demonstrates that cultural hybridity, rather than being a source of tension, provides a robust foundation for subjective well-being. These results contribute to cross-cultural psychology literature by redefining success as an integration of economic achievement and ancestral honor within a pluralistic society Key Words: courtier, Indonesian Chinese businessman, values